Reduced movement of wildlife in Mediterranean landscapes: a case study of brown bears in Greece. (24th February 2020) - de Gabriel Hernando, M.; Karamanlidis, A. A.; Grivas, K.; Krambokoukis, L.; Papakostas, G.; Beecham, J.
Abstract: The survival of large carnivores in a rapidly changing, human‐modified world depends largely on their movements; therefore, understanding how movement patterns change within space and time and which factors affect them most is of paramount importance for their conservation. In a case study in Greece using brown bears Ursus arctos, we evaluated the movement ecology of a recovering population in a Mediterranean landscape, where human activity is high. We found that during daytime bears moved less, when ambient temperatures were high and when they were far away from forests and close to settlements, where human activity is expected to be high. During night‐time, when human activity and mortality risk are expected to be low, bear movement was higher farther from forested areas, close to roads, and in less rough terrain. Although bear movement patterns in Greece were generally similar to those of other bear populations in Europe, home ranges were smaller than in northern populations. These findings indicate that increased human activity and high ambient temperatures reduce bear movement and ultimately contribute to the smaller home ranges in the warmer and human‐dominated Mediterranean landscapes. We suggest that management and conservation actions in Mediterranean landscapes should aim on separating humans and bears in space or time, so that bear movements are not constrained and, in turn, minimum home ranges that cover their essential requirements are guaranteed. Abstract : In a case study in Greece using brown bears, we evaluated the movement ecology of the species in a Mediterranean landscape where human activity is high. We found that increased human activity and high ambient temperatures reduce bear movement and ultimately contribute to the smaller home ranges in the warmer and human‐dominated Mediterranean landscapes. We suggest that management and conservation actions in Mediterranean landscapes should aim at separating humans and bears in space or time, so that bear movements are not constrained and, in turn, minimum home ranges that cover their essential requirements are guaranteed.